ENERGI KONSERVASI PADA POMPA SENTRIFUGAL DENGAN TORQUE FLOW IMPELLER SEMI OPEN DAN CLOSED PADA PENGATURAN KAPASITAS - Siregar, Indra Herlamba (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2020)
Pumps are the most widely used rotating equipment in both the domestic and industrial sectors with a contribution of around 3% of the world's electrical energy usage, in addition to the size of pumps available with many incompatible requirements, it is necessary to regulate their capacity. In this article, there are two capacity setting methods tested, namely valve opening and variable speed drive on semi open and closed centrifugal pump torque flow impeller with blades of 7, 8 and 9. The results explain that in valve opening method the number of blades affects the power consumption pump electricity, although not significant enough, while the variable speed drive method, the number of blades has no effect. However, the power consumption of the impeller closed is lower than the semi open impeller in the valve opening method and there is no significant difference in the variable speed drive method. The capacity setting method with a variable speed drive consumes less electric power than the valve opening method, if the flow of pump more decrease from the initial condition the greater the savings obtained with the variable speed drive method than the valve opening method.